1997
DOI: 10.1177/146642409711700303
|View full text |Cite
|
Sign up to set email alerts
|

Dietary advice in the management of diabetes mellitus - history and current practice

Abstract: Diet has been recognised for over three thousand years as being vital to the overall management of diabetes mellitus (DM). Today dietary advice for the person with diabetes continues to play just as an important role, not just as regards the day to day control but also in respect of the prevention of complications. The history of dietary advice for diabetes is examined as well as current dietary advice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Carbohydrates are the major insulin secretagogues [47] and glycemic control in diabetic subjects is greatly influenced by dietary carbohydrate content. In fact, before the discovery of insulin, dietary carbohydrate restriction was the recommended treatment for diabetes management [48].…”
Section: Low Carbohydrate Diet and Glycemic Controlmentioning
confidence: 99%
“…Carbohydrates are the major insulin secretagogues [47] and glycemic control in diabetic subjects is greatly influenced by dietary carbohydrate content. In fact, before the discovery of insulin, dietary carbohydrate restriction was the recommended treatment for diabetes management [48].…”
Section: Low Carbohydrate Diet and Glycemic Controlmentioning
confidence: 99%
“…The earliest reference to dietary fat intake and diabetes dates back to one of the oldest existing medical documents, the ancient Egyptian Papyrus Ebers, which were written around 1500 BC, approximately 1000 years before the birth of Hippocrates. The Papyrus Ebers recommended a low fat, high carbohydrate diet consisting of wheat, grapes, honey, sweet berries, and beer [2], and a similar diet was recommended by the Cappadocian physician Aretoeus in the second century AD [3]. Although there was no universal diet for treating diabetes, the emphasis had shifted to controlling glycosuria with Thomas Willis, a 17th century English physician who severely restricted calories and presumably fat to control glycosuria [2].…”
Section: History Of Dietary Fat Intake Recommendations and Diabetesmentioning
confidence: 98%
“…In the late 18th century, John Rollo, a surgeon general in the English army treated diabetes with a moderately high fat and relatively low carbohydrate diet that emphasized moderate portions of rancid meats and fat for lunch and dinner, based on the idea that diabetes was caused by a malfunctioning stomach and that rancid meats spared the stomach digestive work, presumably because bacterial action had "predigested" them [2]. However, by the end of the 19th century, portions were further reduced to cut calories in order to better control glycosuria [3].…”
Section: History Of Dietary Fat Intake Recommendations and Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, reducing elevated blood lipids levels has been shown to lower the incidence of acute coronary events in other at-risk populations. Research have shown that before the advent of insulin therapy in the early 20 th century, medical nutrition therapy (MNT) was the only form of therapy for DM [6].…”
Section: Introductionmentioning
confidence: 99%